Cloudera administration handbook : a complete, hands-on guide to building and maintaining large Apache Hadoop clusters using Cloudera Manager and CDH5 /: a complete, hands-on guide to building and maintaining large Apache Hadoop clusters using Cloudera Manager and CDH5. (2014) - Unknown
No abstract available